EFEKTIVITAS PELAKSANAAN PROGRAM LISTRIK PINTAR (PRABAYAR) DI PT. PLN RAYON PANAM KOTA PEKANBARU - Tarida Maharani. Hutasoit; Zulkarnaini " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Implementation of the Smart Electricity Program (Prepaid) at PT. PLN (Persero) Rayon Panam Pekanbaru City has been done since year 2011. In this implementation still there any problems from public, in which costs are burdensome pieces administration of public and policy of the new tide in the compulsory use meter smart electricity (prepaid), and other problems that influence the effectiveness implementation of program. This study aims to determine the effectiveness of implementation of the Smart Electricity Program (Prepaid) and the factors that influence the of the Smart Electricity Program (Prepaid) at PT. PLN (Persero) Rayon Panam Pekanbaru City.Theory used in this study was the effectiveness of the theory put formard by Steers, indicator of effectiveness theory consist of exploiting of resource, satisfaction of job, ability in exploiting, ability live with, and work productivity. This study uses qualitative research methods to study descriptive data. In data collection, researchers using observation, interviews, documentation.Based on the result of the research through interviews and observations, it is known that the of the Smart Electricity Program (Prepaid) at PT. PLN (Persero) Rayon Panam Pekanbaru City is still considered less effective. This means that there are still shortcomings in the implementation of the Smart Electricity Program (Prepaid), in which the factors that affect the effectiveness of implementation of this program are: lack of socialization to public and the community’s ability to adapt in the implementation of the Smart Electricity Program (Prepaid).Keywords: Effectiveness, Smart Electricity Program (Prepaid), Implementation